(untitled) (Journal of Medicine, 2015)
Objective: Patients with chronic renal failure have high burden of cardiovascular morbidity and mortality. This study was carried out to investigate the development of cardiovascular disease in chronic renal failure among female patients on dialysis treatment in Nigeria. Materials and Methods: A total of 40 adult female subjects participated in this study. 20 of them were apparently healthy and served as control group while the rest 20 were female patients with chronic renal failure (CRF) on dialysis treatment. Fasting blood samples were collected and their lipid profile, Total Cholesterol (TC), Triglyceride (TG), High Density Lipoprotein Cholesterol (HDL-C), Low Density Lipoprotein Cholesterol (LDL-C), and Very Low Density Lipoprotein Cholesterol (VLDL-C) were estimated using enzymatic methods. The percentages of these parameters in circulation were obtained. The cardiovascular risk ratios (TC/HDL-C and LDL-C/HDL-C) were calculated. Result: The lipid profile of the chronic renal failure patients (TC 5.70±0.80mmol/l, TG 1.46±0.40mmol/l, LDL-C 3.50±0.2mmol/l, and VLDL-C 0.67±0.2mmol/l) were significantly higher (p<0.05) than that of control group (TC 4.03±0.13mmol/l, TG 1.10± 0.3mmol/l , LDL-C 1.85±0.5mmol/l, and VLDL-C 0.50± 0.01mmol/l) except HDL-C. HDL-C of the CRF patients (1.40±0.2mmol/l) was significantly lower (p<0.05) than that of healthy women (HDL-C 1.70± 0.04mmol/l). These depict no difference in the percentage of VLDL-C & TG in circulation between the control (VLDL C 5% and TG 45%) and chronic renal failure patients (VLDL C 5% and TG 44%). In CRF group, it was observed that 28% of the total plasma lipid (12.73mmol/l) was LDL-C but in healthy women, percentage of LDL-C in circulation (out of 9.18mmol/l) was 20%. It was also observed that 11% of the total plasma lipid (12.73mmol/l) in CRF patients was HDL-C but in healthy subjects, the percentage of HDL-C in circulation (out of 9.18mmol/l) was 19%. The cardiovascular risk indices (TC/HDL-C and LDL-C/HDL-C) of the CRF patients (TC/HDL-C 3.91±0.24 and LDL-C/HDL-C 2.50±0.01) were significantly higher (p<0.05) than those of the healthy subjects (TC/HDL-C 2.40±0.09, LDL-C/HDL-C 1.10±0.08). Conclusion: These results indicate that chronic renal failure is a risk factor to development of cardiovascular disease in female patients on dialysis. DOI: http://dx.doi.org/10.3329/jom.v16i1.22382 J MEDICINE 2015; 16 : 14-17